PENGARUH DIVIDEND PER SHARE, EARNING PER SHARE DAN LOAN TO DEPOSIT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Persada, Gandhi Teguh (Katalogis, 2013)
This research aims to investiagte and analyse simultaneous and partial effects of dividend per share, earning per share and loan to deposit ratio on stock price at banking companies in Indonesia Stock Exchange. Sample of this research covers 12 out of 32 population listed banking companies in Indonesia Stock Exchange. Those samples have been selected using purposive sampling technique. This is a descriptive verificative research using multiple linear regressions as an analysis method. The results show that the effects of dividend per share, earning per share and loan to deposit ratio on stock price is 73.9 % (adjusted R-square) and the rest 26.1 % has been affected by other factors. Simultaneous test of multiple linear regressions indicates that dividend per share, earning per share and loan to deposit ratio perform significant effects on stock price. Partially, dividend per share and loan to deposit ratio do not perform significant on stock price. Meanwhile, earning per share performs significant effect on stock price.